Analysis of Communication Patterns of Mathematical Learning of Blind Students - Bagus hari nugroho; Putri indah lestari (International Journal of Mathematics and Science Education, 2024)
This study aims to analyze communication patterns in mathematics learning for blind students. This research was conducted by utilizing observation techniques on interactions between blind students and teachers in the context of mathematics learning. Data was collected through direct observation and analyzed qualitatively to identify dominant communication patterns. The research results show that communication patterns in mathematics learning for blind students have their own characteristics, which include the use of various verbal and non-verbal methods. This study provides valuable insights for the development of more inclusive learning strategies for students with visual impairments in the context of mathematics education.